A note on Szelenyiopria pampeana (Loiácono) n. comb., parasitoid wasps (Hymenoptera: Diapriidae) attacking the fungus growing ant, Acromyrmex lobicornis Emery (Hymenoptera: Formicidae: Attini) in La Pampa, Argentina - Loiácono, Marta S.; Margaría, Cecilia B. (Zootaxa, 2009)
Diapriids are predominately known as parasitoids of fly pupae. According to Huggert and Masner (1983), representatives of three subfamilies of ants (Myrmicinae, Formicinae and Dorylinae) are the known hosts of myrmecophilic diapriinae wasps (Diapriidae: Diapriinae); within the Myrmicinae, the genera known to be associated with diapriines are Solenopsis Westwood, Tetramorium Mayr and possibly Myrmica Latreille. Acromyrmex ambiguus (Emery) (Myrmicinae), is known as larval host of Szelenyiopria lucens (Loiácono) (Loiácono 1987). Masner and García (2002) noted that this is the first member of the tribe Diapriini in the New World to be positively reared from ants. Gymnopria pampeana Loiácono was reared from A. lobicornis Emery in Argentina (Loiácono et al. 2000). Fernández Marin et al. (2006) provided details of the biology of the diapriine wasps Acanthopria spp. and Mimopriella sp., both of which attack larvae of Cyphomyrmex fungus-growing ants.